Expression and analysis of the SAM‐dependent RNA methyltransferase Rsm22 from Saccharomyces cerevisiae. Issue 6 (24th May 2021) - Alam, Jahangir; Rahman, Farah Tazkera; Sah-Teli, Shiv K.; Venkatesan, Rajaram; Koski, M. Kristian; Autio, Kaija J.; Hiltunen, J. Kalervo; Kastaniotis, Alexander J.
Abstract : Rsm22‐family proteins are conserved putative SAM‐dependent methyltransferases with important functions in mitochondrial translation. Here, the results of a comparative bioinformatics analysis of Rsm22‐type proteins are presented, the expression, biophysical characterization and crystallization of Saccharomyces cerevisiae Rsm22 are reported, a low‐resolution SAXS structure of the protein is revealed, and SAM‐dependent RNA methyl transferase activity of the protein is demonstrated. Abstract : The Saccharomyces cerevisiae Rsm22 protein (Sc‐Rsm22), encoded by the nuclear RSM22 (systematic name YKL155c ) gene, is a distant homologue of Rsm22 from Trypanosoma brucei (Tb‐Rsm22) and METTL17 from mouse (Mm‐METTL17). All three proteins have been shown to be associated with mitochondrial gene expression, and Sc‐Rsm22 has been documented to be essential for mitochondrial respiration. The Sc‐Rsm22 protein comprises a polypeptide of molecular weight 72.2 kDa that is predicted to harbor an N‐terminal mitochondrial targeting sequence. The precise physiological function of Rsm22‐family proteins is unknown, and no structural information has been available for Sc‐Rsm22 to date. In this study, Sc‐Rsm22 was expressed and purified in monomeric and dimeric forms, their folding was confirmed by circular‐dichroism analyses and their low‐resolution structures were determined using a small‐angle X‐ray scattering (SAXS) approach. The solution structure of the monomeric form of Sc‐Rsm22 revealed an elongated three‐domain arrangement, which differs from the shape of Tb‐Rsm22 in its complex with the mitochondrial small ribosomal subunit in T. brucei (PDB entry 6sg9 ). A bioinformatic analysis revealed that the core domain in the middle (Leu117–Asp462 in Sc‐Rsm22) resembles the corresponding region in Tb‐Rsm22, including a Rossmann‐like methyltransferase fold followed by a zinc‐finger‐like structure. The latter structure is not present in this position in other methyltransferases and is therefore a unique structural motif for this family. The first half of the C‐terminal domain is likely to form an OB‐fold, which is typically found in RNA‐binding proteins and is also seen in the Tb‐Rsm22 structure. In contrast, the N‐terminal domain of Sc‐Rsm22 is predicted to be fully α‐helical and shares no sequence similarity with other family members. Functional studies demonstrated that the monomeric variant of Sc‐Rsm22 methylates mitochondrial tRNAs in vitro . These data suggest that Sc‐Rsm22 is a new and unique member of the RNA methyltransferases that is important for mitochondrial protein synthesis.